A Watch Tower for Disease Control The National High Security Animal Disease Laboratory - Bhatia, Sandeep; Pateriya, Atul; Sood, Richa (Indian Farming, 2015)
The National High Security Animal Disease Laboratory is an excellent example of biosafetyengineering where research is conducted on dangerous pathogens only after considering all pros and cons of human and animal safety.